Shear Effects on Aluminum Phosphate Adjuvant Particle Properties in Vaccine Drug Products. Issue 2 (29th August 2014) - Kolade, Olatomirin O.; Jin, Wenbin; Tengroth, Charbel; Green, Kenneth D.; Bracewell, Daniel G.
<x xml:space="preserve">Abstract</x> Adjuvant‐containing drug products can be exposed to high levels of interfacial shear during manufacture. This may affect the integrity of the adjuvant, alter its interaction with the drug substance or change the physical characteristics of the drug product. In this study, a solid–liquid interfacial shear device was used to investigate the shear response of aluminum phosphate adjuvant alone and two adjuvant containing vaccine drug products (DP1 and DP2). The relationship between the shear sensitivity of each and its resuspension properties was determined. Changes in the particle dimensions of the bulk adjuvant were minimal at shear strain rates of 10, 900 s−1. However, at 25, 500 s−1, the median particle diameter was reduced from 6.2 to 3.5 μm and was marked by the presence of sub‐micron fines. A formulation without drug substance and DP2 produced similar shear responses but with less impact on particle diameter. The behavior of DP1 was less predictable. Sheared DP1 was characterized by prolonged sedimentation because of the presence of fine particulates and required in excess of 300 rotations to resuspend after extended storage. The study confirms that the solid–liquid interfacial shear device may be applied to understand product shear sensitivity associated with vaccine manufacturing. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:378–387, 2015